Arterial stiffness, pressure and flow pulsatility and brain structure and function: the Age, Gene/Environment Susceptibility--Reykjavik study - Mitchell, Gary F; van Buchem, Mark A; Sigurdsson, Sigurdur; Gotal, John D; Jonsdottir, Maria K; Kjartansson, Ólafur; Garcia, Melissa; Aspelund, Thor; Harris, Tamara B; Gudnason, Vilmundur; Launer, Lenore J (Brain (London, England : 1878), 2011)
Aortic stiffness increases with age and vascular risk factor exposure and is associated with increased risk for structural and functional abnormalities in the brain. High ambient flow and low impedance are thought to sensitize the cerebral microcirculation to harmful effects of excessive pressure and flow pulsatility. However, haemodynamic mechanisms contributing to structural brain lesions and cognitive impairment in the presence of high aortic stiffness remain unclear. We hypothesized that disproportionate stiffening of the proximal aorta as compared with the carotid arteries reduces wave reflection at this important interface and thereby facilitates transmission of excessive pulsatile energy into the cerebral microcirculation, leading to microvascular damage and impaired function. To assess this hypothesis, we evaluated carotid pressure and flow, carotid-femoral pulse wave velocity, brain magnetic resonance images and cognitive scores in participants in the community-based Age, Gene/Environment Susceptibility--Reykjavik study who had no history of stroke, transient ischaemic attack or dementia (n = 668, 378 females, 69-93 years of age). Aortic characteristic impedance was assessed in a random subset (n = 422) and the reflection coefficient at the aorta-carotid interface was computed. Carotid flow pulsatility index was negatively related to the aorta-carotid reflection coefficient (R = -0.66, P<0.001). Carotid pulse pressure, pulsatility index and carotid-femoral pulse wave velocity were each associated with increased risk for silent subcortical infarcts (hazard ratios of 1.62-1.71 per standard deviation, P<0.002). Carotid-femoral pulse wave velocity was associated with higher white matter hyperintensity volume (0.108 ± 0.045 SD/SD, P = 0.018). Pulsatility index was associated with lower whole brain (-0.127 ± 0.037 SD/SD, P<0.001), grey matter (-0.079 ± 0.038 SD/SD, P = 0.038) and white matter (-0.128 ± 0.039 SD/SD, P<0.001) volumes. Carotid-femoral pulse wave velocity (-0.095 ± 0.043 SD/SD, P = 0.028) and carotid pulse pressure (-0.114 ± 0.045 SD/SD, P = 0.013) were associated with lower memory scores. Pulsatility index was associated with lower memory scores (-0.165 ± 0.039 SD/SD, P<0.001), slower processing speed (-0.118 ± 0.033 SD/SD, P<0.001) and worse performance on tests assessing executive function (-0.155 ± 0.041 SD/SD, P<0.001). When magnetic resonance imaging measures (grey and white matter volumes, white matter hyperintensity volumes and prevalent subcortical infarcts) were included in cognitive models, haemodynamic associations were attenuated or no longer significant, consistent with the hypothesis that increased aortic stiffness and excessive flow pulsatility damage the microcirculation, leading to quantifiable tissue damage and reduced cognitive performance. Marked stiffening of the aorta is associated with reduced wave reflection at the interface between carotid and aorta, transmission of excessive flow pulsatility into the brain, microvascular structural brain damage and lower scores in various cognitive domains.